Gaps critical for the survival of exposed seeds during Cerrado fires - Daibes, L. Felipe [UNESP] (2018)
The fine-scale effects of fire and the consequences for seed survival are poorly understood, especially in the Cerrado (Brazilian savannas). Thus, we investigated whether vegetation gaps (bare soil patches) influence the survival of exposed seeds during fire events in the Cerrado by serving as safe sites. We performed field fire experiments in Central Brazil to examine how gap size (% of bare soil) influences fire heat (fire temperatures and residence time) and seed survival (Experiment 1) and to determine how seed survival is affected by fixed conditions: gaps vs grass tussocks during fires (Experiment 2). We used seeds of two common Cerrado legumes, Mimosa leiocephala Benth. and Harpalyce brasiliana Benth. Seed survival was analysed using GLMMs with a binomial distribution. In Experiment 1, seeds survived (38 and 35% for M. leiocephala and H. brasiliana respectively) only when the gaps had >40% of bare soil. In Experiment 2, all seeds under grass tussocks died when exposed to fire, whereas up to 40% of seeds survived in vegetation gaps, relative to their respective controls. Because vegetation gaps influence fire heat, they are important as safe sites for seed survival in the Cerrado, allowing a significant proportion of seeds to survive when exposed at the soil surface.